Mapping lateral extent of Suevites at Northern Part of Lake Bosumtwi using resistivity and seismic refraction methods - Habimana, Emmanuel (2016)
A thesis submitted to the Department of Physics, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Philosophy (Geophysics),